Hubungan Usia, Tingkat Pendidikan dan Status Pekerjaan dengan Tingkat Kecemasan Ibu Hamil Primigravida dalam Menghadapi Persalinan - Nafisah, Durratun; Susanto, Herry; Wahyuni, Sri; Khasanah, Nopi Nur (Jurnal Gema Keperawatan, 2025)
Anxiety before childbirth is a common psychological condition experienced by pregnant women, especially those in their first pregnancy (primigravida), due to a lack of experience, limited knowledge, and insufficient emotional support. If left unaddressed, anxiety can negatively affect both maternal and fetal health, including increased risks of preterm birth and developmental issues. This study aims to determine the prevalence of anxiety and its associated demographic factors among primigravida women. This research uses a correlational study design with a cross-sectional approach. A total of 93 third-trimester primigravida women were selected using a total sampling technique. Data were collected using the Perinatal Anxiety Screening Scale (PASS) questionnaire and analyzed descriptively and inferentially using the chi-square test. The results showed that 32,3% of respondents experienced mild anxiety, 48,4% moderate anxiety, and 19,3% severe anxiety. The study found a significant relationship between education level (p=0.009) and employment status (p=0,009) with anxiety levels, while age did not show a significant association (p=0,143). These findings highlight the importance of integrating psychological screening into antenatal care services and developing community-based educational interventions to reduce maternal anxiety early in pregnancy.